Development and optimization of fast, efficient, economical and green HPLC method for ibuprofen impurities testing by use of core-shell column - Piponski, Marjan; Bakovska Stoimenova, Tanja; Logoyda , Liliya; Topkoska, Marina; Lazarevska Todevska, Elena; Petrovska, Elena; Angelevski, Stefan (Archives of Pharmacy, 2022)
Ibuprofen is still very often used nonsteroidal anti-inflammatory drug, beside the fact that its origin dates a half century ago. This is one of the reasons for continuous improvement of its quality control analytical methods. Current pharmacopoeial monographs for ibuprofen prescribe HPLC method for impurities testing by use of C18 column (150 mm × 4.6 mm, 5 µm), gradient elution at flow rate of 2 mL/min and run time of about 80 minutes. In a bunch of core-shell particle columns from different vendors, with different physico-chemical characteristics, inducing different intensity of interactions between analyte and stationary phase, a proper separation and system suitability parameters, could be achieved only with some selected ones. This indicates that beside incomparable separation characteristics between 5 µm fully porous and 2.7 µm core-shell particles, it did not warrant successful separation and simple replacement of monograph recommended standard column with any of modern powerful core-shell particles columns. Thus, we followed to investigate and calculate the benefits of replacement. By use of samples and standards prepared in accordance to monographs, we tested few more powerful new core-shell columns, with different length, diameter, particle size and different vendors. The best results were achieved with Shimadzu C18 Next Leaf SH-SPP and Poroshell C18, both with 2.7 µm particles, which reduced the run time by 7-8 times, when compared to the pharmacopoeial method. Beside shortening run time, this method offers many advantages from economic and ecological aspects, and increases sensitivity and resolution to significantly improved values.